Dynamic accumulation of sesquiterpenes in essential oil of Pogostemon cablin - Chen,Ying (2014)
Sesquiterpenes Essential oil produced by patchouli was one of the most important naturally occurring base materials used in the perfume industry, containing various sesquiterpenes. Three different parts (leaves, stems and roots) of Pogostemon cablin (Blanco) Benth., Lamiaceae, were profiled in relation to different maturation phases in this paper, evaluating the variations in content of the major sesquiterpenes in the essential oil. Twelve sesquiterpenes were analyzed by GC-MS throughout the maturity of P. cablin. Patchouli alcohol (37.54%-51.02% in leaves, 28.24%-41.96% in stems and 14.55%-35.12% in roots) was the major sesquiterpene during the maturation of the plant. The average content of several other sesquiterpenes (α-bulnesene, α-guaiene, seychellene, β-humulene and caryophyllene) were higher than 3% among leaves, stems and roots. The content of essential oil, patchouli alcohol, α-bulnesene and several other compounds were highly accumulated at 210 days of maturation after cultivation of P. cablin. Thus, this period was the best moment to exploit the maximum level of these high value-added compounds in P. cablin. Furthermore, our results indicated that the essential oil extracted from leaves of P. cablin has the highest potential to be used in the perfume industry.